Employing modern teaching methods in teaching Islamic jurisprudence Its importance and methods - AOUMAR, Salah (Journal of Human Sciences, 2025)
This research focuses on how to employ modern teaching methods in the educational process for teaching Islamic jurisprudence. The one who is still dominated by traditional methods that do not satisfy the thirst of the student, and hinder serious academic achievement and excellence.The aim of the study is to try to find the optimal ways to employ modern teaching methods in supporting the quality of teaching Islamic jurisprudence. In order to achieve the idea of modern education that aims to integrate traditional teaching methods with modern educational approaches.The study has concluded to results, most notably; the importance of employing modern teaching methods in teaching Islamic jurisprudence, and benefiting from its numerous and diverse advantages. As indicated by a set of appropriate practical mechanisms that combine the preservation of the authenticity of Islamic knowledge, and the benefit of modern methods that facilitate the process of education. As the study highlighted the importance of the teacher, and that modern teaching methods cannot eliminate his position. His presence remains essential and very important, as he is the first direct contact in the education process.